2016
DOI: 10.12681/mms.1760
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and secondary production of Donax trunculus (Mollusca, Bivalvia) in the Gulf of Annaba (Northeast Algeria)

Abstract: The population dynamics and secondary production of the wedge clam Donax trunculus were studied in the Gulf of Annaba (Northeast Algeria) monthly for one year at a site close to the Annaba port and the Seybouse river, affected by industrial and agricultural pollution (Sidi Salem), and at a site more distant from major pollution sources, but exploited by fishery (Echatt). The number of individuals (N) was lower at Sidi Salem (36–148 ind m-2) than at Echatt (63–272 ind m-2) in most sampling dates, while the biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…The highest growth rate in length was found in 5-10 mm length group. Neuberger-Cywiak et al, (1990) found similar results and reported the highest growth rate at the first 2.5 months, and Hafsaoui et al, (2016) reported the highest growth rate within the first year. Individuals within the length group 25-30 mm constitutes 20.75 % of overall samples.…”
Section: Growth Ratesupporting
confidence: 57%
See 1 more Smart Citation
“…The highest growth rate in length was found in 5-10 mm length group. Neuberger-Cywiak et al, (1990) found similar results and reported the highest growth rate at the first 2.5 months, and Hafsaoui et al, (2016) reported the highest growth rate within the first year. Individuals within the length group 25-30 mm constitutes 20.75 % of overall samples.…”
Section: Growth Ratesupporting
confidence: 57%
“…There are various studies conducted on wedge clam from the Atlantic Ocean (Bayed & Guillou, 1985;Bayed, 1991Bayed, , 1998Guillou & Bayed, 1991) and from the Mediterrranean Sea (Mouëza, 1972;Mouëza & Chessel, 1976;Ansell & Bodoy, 1979;Neuberger-Cywiak et al, 1990;Deval, 2009;Hafsaoui et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The size classifications of blood clams in Kendari Bay were less diverse compared to those of other species in other estuaries, such as Cerastoderma edule (Callaway et al 2013), Darina solenoides (Lizarralde et al 2018), each consisting of 4 age groups, as well as beach clams, namely Donax trunculus (Hafsaoui et al 2016) and Circenita callipyga with 3 and 3-4 age groups, respectively (Bagher et al 2007). However, the group composition obtained had little difference from the Pokea clams exploited in the Pohara River and Lasolo River, each having 2 and 3 size categories (Bahtiar et al 2018).…”
Section: August Februarymentioning
confidence: 99%
“…Kepadatan kerang pokea selama penelitian di Sungai Pohara Kepadatan pokea di Sungai Pohara yang ditemukan berada pada kondisi yang relatif sama dengan kerang yang sama di Sungai Lasolo (Bahtiar et al, 2018), dan beberapa kepadatan jenis kerang lainnya seperti: Cerastoderma edule (Callaway et al, 2013), Mesodesma mactroides Hermann et al, 2010), Anomalocardia brasiliana (Rodrigues et al, 2013). Namun kepadatan kerang pokea jauh lebih tinggi dibandingkan bivalvia lainnya seperti: Donax trunculus (Hafsaoui et al, 2016), Anomalocardia brasiliana (Mattos & Cardoso 2012;, tetapi jauh lebih rendah pada spesies yang invasif seperti: Dreissena polymorpha (Kobak, 2005) Anomalocardia brasiliana (Corte et al, 2015)…”
Section: Kepadatan Kerang Pokeaunclassified